MEASURING Five-big Personality Factors of the employees - Abbas, Roaa; Raheem, AbdulHalim (Al-Adab Journal, 2023)
The current study aims at measuring the five major factors of personality The Five bigPersonality Factors of employees according to the gender variable, job status and age, research sample is: 400 employees and a job status (contract - permanent), and the age (30 or less - more than 30) years, from the state ministries in Baghdad province following the stratified random meth. search tool, the Costa & McCrae scale (1992) Al-Ansari Arabization (1997) is adopted. then the psychometric properties of the two measures were extracted. The research output: staff have low neurological significance with statistically significant, extensibility, acceptability, and openness On experience, the vitality of the conscience is high, statistically significant, and there is no diferences in the vitality of,the conscience, acceptability and nervousness according to the gender variable except the extensibility and openness to experience and it is in the interest of females, and there is no diferences in neuroticism, openness to experience, acceptability, and h Conscience of the conscience according to the age variable except the extrapolation factor and is in favor of 30 years or less, and there are no differences in the interaction between the variables (gender, job status, age).